Penang economic relationship with Kedah and Selangor: a follow-up research based on the correspondence with Francis Light during the quarter end of the 18th century - Ibrahim Ahmad,; Aizat Khairi,; Zamri Hashim,; Shariff Harun, (Penerbit Universiti Kebangsaan Malaysia, 2025)
A collection of correspondence of Francis Light is the outcome of the Malay writing system that acquires main attention as a trading history source in the Malay Archipelago. This is due to the fact that the correspondence that is written or received by Francis Light could be able to depict the real political, economic and social situation of that time frame. In terms of economy, the correspondence of Francis Light could provide a clearer information on the trading regulations and types of goods of the Malay Isles that trade with Penang. Therefore, this paper will have a closer look on few businesses correspondence that are received by Francis Light from Sultan and Commander of both states when he was the Governor in Penang since 1786. Majority of the correspondence clearly stated the business matters, logistics and selling of commodities, weapons, slaves, and opium. The content of the correspondence not just visualized British as respected administrator but also explained the existence of 18th Century business diversity. In conclusion, the collection of correspondence of Francis Light is one important written history source for both states thus becoming the beginning of British occupation in other Malay states.